Management of Skeletal Class II Malocclusion in Non-Complaint Patient using Powerscope - A Case Report - Ansari, Akram; Jain, Abhay Kumar; Singh, Ankit; Sharma, Priya; Adil, Muneeb (Orthodontic Journal of Nepal, 2019)
Class II malocclusion in pubertal phase presents a major and a common challenge to orthodontists. Proper diagnosis and treatment planning in early stage help in preventing and intercepting the severity of malocclusion. In pubertal phase skeletal Class II malocclusion due to mandibular retrusion are best treated with functional appliance. In recent time PowerScope fixed functional appliance is gaining immense popularity as noncompliant Class II corrector. In the present case report an adolescent male patient having Class II division 1 malocclusion with functional jaw retrusion was treated using MBT 0.022” prescription and PowerScope appliance. 7-8 months of PowerScope wear obtained stable and successful results with improvement in facial profile, skeletal jaw relationship and mild increase in IMPA. It can thus be concluded that PowerScope gives good results in Class II correction with a combination of patient comfort and ease of use that was unmatched among other appliances